The role of iron nitrides in the Fe–N–C catalysis system towards the oxygen reduction reaction - Wang, Min; Yang, Yushi; Liu, Xiaobo; Pu, Zonghua; Kou, Zongkui; Zhu, Peipei; Mu, Shichun (Nanoscale, 2017)
Fe-N-C series catalysts are always attractive for their high catalytic activity towards the oxygen reduction reaction (ORR). However, they usually consist of various components such as iron nitrides, metallic iron, iron carbides, N-doped carbon and Fe-N moieties, leading to controversial contributions of these components to the catalysis of the ORR, especially iron nitrides. In this work, to investigate the function of iron nitrides, Fe N nanoparticles (NPs) embedded in mesoporous N-doped carbon without Fe-N moieties are designed and constructed by a simple histidine-assisted method. Herein, the use of histidine can increase the N and Fe contents in the product. The obtained catalyst exhibits excellent ORR catalytic activity which is very close to that of the commercial Pt/C catalyst in alkaline electrolytes. Combining the catalytic activity, structural characterization (especially from Mössbauer spectroscopy), and the results of DFT calculations for adsorption energies of oxygen on the main surfaces of Fe N including ε-Fe N and ζ-Fe N, it can be deduced that Fe N NPs as active species make a contribution to the ORR catalysis, of which ε-Fe N (x ≤ 2.1) is more active than ζ-Fe N. In addition, we find that there exists an obvious synergistic effect between Fe N NPs and N-doped carbon, leading to the greatly enhanced ORR catalytic activity.